Carboxyl Surface Functionalization of Poly(L‐lactic acid) Electrospun Nanofibers through Atmospheric Non‐Thermal Plasma Affects Fibroblast Morphology. Issue 3 (27th December 2013) - Dolci, Luisa Stella; Quiroga, Santiago David; Gherardi, Matteo; Laurita, Romolo; Liguori, Anna; Sanibondi, Paolo; Fiorani, Andrea; Calzà, Laura; Colombo, Vittorio; Focarete, Maria Letizia
<x xml:space="preserve">Abstract</x> In this study, atmospheric pressure non‐thermal plasma treatment of electrospun poly(L‐lactic acid) scaffolds is used to improve scaffold hydrophilicity and to introduce carboxyl groups on scaffold surface. Thermo‐mechanical properties, morphology, hydrophilicity, and water uptake of the plasma‐treated scaffolds are studied. The amount of carboxyl functional groups on the scaffold surface is evaluated using fluorescein isothiocyanate conjugation and microdensitometry. The effect of plasma treatment on mouse embryonic fibroblast morphology is assessed through image analysis. Results show an enhancement of scaffold biocompatibility, demonstrating that atmospheric plasma technology is a flexible process that can be integrated in "in‐line" procedures of biomaterial fabrication and functionalization.<inline-graphic xlink:href="ark:/27927/pgg4sxzdt1k" content-type="ppap201300104-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />